Customized ICC display profile construction and concerns - (:unkn) unknown (My University, 2010)
With the advent of modern digital technology, users can capture an image and reproduce it between different media, such as to display it on LCD or CRT monitor, print it on desktop printer, or send it to a printing press. The challenge is then to maintain the accuracy of image colors during this reproduction. This has led to the development of color management systems. Using these systems, the color reproduction across media is accomplished using device ICC profiles that describe each device's color characterization data in a standardized format in terms of a device independent color space (profile connection space or PCS).
Keywords: Gamma; ICC; LCD; Matrix; Monitor